Description of the embryonic development of the small and large intestine of the Wistar rat compared to humans. Literature review - Moreno-Gomez , Freddy (2023)
This literature review provides a comprehensive description of the developmental biology of the small and large intestines in both Wistar rats and humans. A comparison was made between the embryology at different levels of biological organization, including organs, tissue structures, tissues, cellular structures, and cells. The key parameter considered for comparison was the development time (in days), as there is no consensus that allows direct extrapolation of the small and large intestine development between both species.To conduct this review, a systematic literature search was performed in MedLine, utilizing PubMed and combining the keywords "Developmental biology", "small intestine", "large intestine" and "Wistar rat". The information gathered from the 10 articles included in the discussion about the embryonic development of the Wistar rat's small and large intestines was then contrasted with descriptions from classic books on human developmental biology. The proposed developmental consensus could prove highly valuable for future research, particularly in the context of translational medicine, where the Wistar rat biomodel plays a crucial role.